Improvement of physical and sensory quality of beef patties with the addition of chicken eggshells nanopowder - Evanuarini, Herly; Susilo, Agus; Yanuhar, Uun; Kurniawati, Adelya Desi (Universitas Sebelas Maret, 2023)
Objective: The purpose of this study was to investigate the effect of adding chicken eggshells nanopowder for the physical quality and sensory evaluation of beef patties.Methods: The method used in this study was a laboratory experiment with a completely randomized design with 5 treatments: without adding chicken eggshells nanopowder as a control, adding 0.1%, 0.3%, 0.5% and 0.7% chicken eggshells nanopowder (w/w) with 5 repetitions. Data were analyzed by analysis of variance, if there was a significant or very significant difference it was continued with Duncan's multiple range test.Results: Based on the research results, it was found that the addition of chicken eggshells nanopowder to beef patties had a very significant effect (P<0.01%) on moisture content, water holding capacity, cooking loss, texture, and sensory evaluation.Conclusions: The addition of 0.7% chicken eggshells nanopowder can reduce moisture content, increase water holding capacity, reduce cooking loss, improve texture, and sensory quality acceptable to panelists.